The Influence Of Need For Achievement, Locus Of Control And Self Efficacy On Interest In Entrepreneurship - Nabilah, Salma; Sadiah, Ati; Srigustini, Astri (FKIP Universitas Lampung, 2023)
This research aims to determine the influence of Need for Achievement, Locus of Control and Self Efficacy on Entrepreneurial Interest. This research uses a survey research method with a quantitative approach. The population of students at SMK Negeri 2 Tasikmalaya is 2,649 people. The sampling technique used was the Proportionate Stratified Random Sampling technique. So the total sample taken was 348 people according to the researchers' considerations. Data collection techniques in this research used questionnaires, statistical tests used multiple linear regression analysis. The research results show that: 1) Need for Achievement has a positive and significant effect on students' entrepreneurial interest. 2) Locus of Control has a positive and significant effect on students' interest in entrepreneurship. 3) Self Efficacy has a positive and significant effect on students' interest in entrepreneurship. 4) Need for Achievement, Locus of Control and Self Efficacy have a positive and significant effect on students' interest in entrepreneurshipKeywords: Interest in Entrepreneurship, Locus of Control, Need for Achievement, Self efficacyDOI: http://dx.doi.org/10.23960/E3J/v6i2.168-175